2019
DOI: 10.1002/nau.24123
|View full text |Cite
|
Sign up to set email alerts
|

Improving clinical outcomes with lower motor voltage (≤3 V) during stage 1 sacral neuromodulation for interstitial cystitis or bladder pain syndrome

Abstract: Aims We desire to evaluate whether utilization of ≤3 V (new experimental approach) vs the traditional four or more volts for lead motor response during stage 1 sacral neuromodulation may impart an improvement in voiding and pain parameters. Methods An observational, retrospective, double cohort review was conducted of 179 female patients who experienced medically recalcitrant interstitial cystitis (IC) or bladder pain syndrome (BPS) between January 2002 and January 2013. Group A included 105 women with a motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
(80 reference statements)
0
18
0
Order By: Relevance
“…The opposite was true for pain reduction. Marinkovic 34 found greater reductions in symptoms when administering less than 3 V compared to more than 4 V.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The opposite was true for pain reduction. Marinkovic 34 found greater reductions in symptoms when administering less than 3 V compared to more than 4 V.…”
Section: Resultsmentioning
confidence: 97%
“…Four studies showed that sacral neuromodulation can be effective at reducing symptom scores 33‐35,37 . Five studies found that sacral neuromodulation can decrease pain and voiding frequency 34‐38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICBPS is a disease of unknown etiology, with symptoms of intermittent or chronic pelvic pain and lower urinary tract symptoms such as frequency and urgency. Several therapeutic options are introduced, but none of them improves completely all the symptoms (Marinkovic, 2019). Thus, understanding the pathophysiology of ICBPS could be a milestone in the search for successful treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Medically recalcitrant cases may be suitable for sacral neuromodulation. Success rates, particularly with optimized protocols to include motor response with low (≤3 V) voltage stimulation, can produce clinical benefit, with a reduction in visual analogue pain scores and validated symptom questionnaire scores in up to 95% of patients [19].…”
mentioning
confidence: 99%